2018
DOI: 10.1080/24694452.2018.1426436
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Objective Hurricane Risks and Community Resilience on Risk Perceptions of Hurricanes at the County Level in the U.S. Gulf Coast: An Innovative Approach

Abstract: Communities' risk perceptions can influence their abilities to cope with coastal hazards such as hurricanes and coastal flooding. Our study presents an initial effort to examine the relationship between community resilience and risk perception at the county level, through innovative construction of aggregate variables. Utilizing the 2012 Gulf Coast Climate Change Survey merged with historical hurricane data and community resilience indicators, we first apply a spatial statistical model to construct a county-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Further, conventional surveys focus on the variations among individuals while public policies are designed and implemented at an aggregate level. This mismatch on geographic scales naturally creates a gap between research results obtained from surveys and actionable policy items (Shao et al, 2018). Due to the time consuming and costly procedures, traditional surveys are conducted only at discrete points of time with a coarse temporal scale.…”
mentioning
confidence: 99%
“…Further, conventional surveys focus on the variations among individuals while public policies are designed and implemented at an aggregate level. This mismatch on geographic scales naturally creates a gap between research results obtained from surveys and actionable policy items (Shao et al, 2018). Due to the time consuming and costly procedures, traditional surveys are conducted only at discrete points of time with a coarse temporal scale.…”
mentioning
confidence: 99%
“…Event trends have also been included in models predicting perceptions of weather events. Goebbert et al Evidence for a recency bias has also been demonstrated through research on perceptions of changes in hurricane strength, consistent with research showing that recent experiences may be more influential to perceptions than trends over time (Weber 2010;Shao et al 2016).…”
Section: Geographic and Biophysical Influences On Risk Perceptionsmentioning
confidence: 62%
“…Educational attainment typically exerts a direct influence on concern about environmental issues, such that more educated individuals tend to express greater concerns or risk perceptions (Dunlap and Van Liere 1984;Jones and Dunlap 1992). Education and scientific literacy, however, also interact with politics, such that higher educational attainment among self-identified Republicans or political conservatives corresponds to lower perceived risks and less concern about environmental issues, which may indicate motivated reasoning (Hamilton 2008;Hamilton et al 2012;Hamilton and Saito 2015;McCright and Dunlap 2011;McCright 2011;Krosnick et al 2000;Malka et al 2009;Shao et al 2014).…”
Section: B Individual-level Influences On Risk Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations